Risk factors, clinical correlates, and social functions of Chinese schizophrenia patients with drug-induced parkinsonism: A cross-sectional analysis of a multicenter, observational, real-world, prospective cohort study - Weng, Jiajun; Zhang, Lei; Yu, Wenjuan; Zhao, Nan; Zhu, Binggen; Ye, Chengyu; Zhang, Zhanxing; Ma, Changlin; Li, Yan; Yu, Yiming; Li, Huafang (Frontiers in Pharmacology, 2023)
Aim: To explore the risk factors, clinical correlates, and social functions of Chinese schizophrenia patients with DIP. Methods: A cross-sectional analysis of a multicenter, observational, real-world, prospective cohort study of the Chinese schizophrenia population was conducted, with a baseline assessment from the year 2012 to 2018 and participants recruited from four mental health centers in Shanghai. In total there were 969 objects analyzed. Sociodemographic data, drug treatment, and clinical variables were compared between the DIP group and the non-DIP group. Variables that correlated with the induction of DIP and variables which P < 0.1 during comparison were included in the binary logistic model analyzing the risk factors of DIP. First generation antipsychotics (FGA)/second generation antipsychotics (SGA) model and high/low or medium D2 receptor antipsychotics were analyzed respectively to control the bias of co-linearity. All risk factors derived from the model above, clinical variables which P<0.1 were included in the multivariate analysis of clinical correlates and social function of DIP patients. The Positive and Negative Syndrome Scale (PANSS) model and The Personal and Social Performance (PSP) model were analyzed separately to control the bias of co-linearity. Conclusions: Age, high D2 receptor antagonistic antipsychotic dose, and the valproate dose are the risk factors for DIP. DIP is significantly correlated with psychiatric symptoms and social performance of Chinese schizophrenia patients. Elder age is also a related factor to psychotic symptoms and social adaption in Chinese schizophrenic patients. The rational application and discontinuation of valproate acid are necessary. Early intervention and treatment of DIP can improve the prognosis and social performance of schizophrenia patients.